Natural history of elderly-onset inflammatory bowel disease: a population-based cohort study. Issue 3 (13th February 2013) - Charpentier, Cloé; Salleron, Julia; Savoye, Guillaume; Fumery, Mathurin; Merle, Véronique; Laberenne, Jean-Eric; Vasseur, Francis; Dupas, Jean-Louis; Cortot, Antoine; Dauchet, Luc; Peyrin-Biroulet, Laurent; Lerebours, Eric; et al.
Abstract : Data on the natural history of elderly-onset inflammatory bowel disease (IBD) are scarce. Methods: In a French population-based cohort we identified 841 IBD patients >60 years of age at diagnosis from 1988 to 2006, including 367 Crohn's disease (CD) and 472 ulcerative colitis (UC). Results: Median age at diagnosis was similar for CD (70 years (IQR: 65–76)) and UC (69 years (64–74)). Median follow-up was 6 years (2–11) for both diseases. At diagnosis, in CD, pure colonic disease (65%) and inflammatory behaviour (78%) were the most frequent phenotype. At maximal follow-up digestive extension and complicated behaviour occurred in 8% and 9%, respectively. In UC, 29% of patients had proctitis, 45% left-sided and 26% extensive colitis without extension during follow-up in 84%. In CD cumulative probabilities of receiving corticosteroids (CSs), immunosuppressants (ISs) and anti tumor necrosis factor therapy were respectively 47%, 27% and 9% at 10 years. In UC cumulative probabilities of receiving CS and IS were 40% and 15%, respectively at 10 years. Cumulative probabilities of surgery at 1 year and 10 years were 18% and 32%, respectively in CD and 4% and 8%, respectively in UC. In CD complicated behaviour at diagnosis (HR: 2.6; 95% CI 1.5 to 4.6) was associated with an increased risk for surgery while CS was associated with a decreased risk (HR: 0.5; 0.3 to 0.8). In UC CS was associated with an increased risk (HR: 2.2; 1.1 to 4.6) for colectomy. Conclusions: Clinical course is mild in elderly-onset IBD patients. This information would need to be taken into account by physicians when therapeutic strategies are established.